Problematika Investor State Dispute Settlement dalam Bilateral Investment Treaty Indonesia-Singapura 2018 - Zulkarnain, Mukhamad (State of Islamic Institute Langsa, 2023)
The signing of the 2018 Indonesia-Singapore BIT is a new chapter for Indonesia in establishing international relations in the field of investment after in 2013 Indonesia stopped the 2005 Indonesia-Singapore BIT because it was more in favor of foreign investors. This alignment is contained in the Investor State Dispute Settlement (ISDS) mechanism where the dispute resolution mechanism is also regulated in the 2018 Indonesia-Singapore BIT even though it is known that the ISDS mechanism has many shortcomings and provides protection for foreign investors. Therefore, there is a need for a new alternative to perfect the ISDS mechanism. Normative juridical methods are used in this writing by qualitatively analyzing the data. The results of the study concluded that the ISDS mechanism in the Indonesia-Singapore BIT 2018 has not been able to protect Indonesia's interests in international investment cooperation and requires an Investment Court System (ICS) mechanism to perfect the ISDS mechanism.